2016
DOI: 10.1007/s11418-015-0961-1
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, aroma evaluation, and inhibitory activity towards acetylcholinesterase of essential oils from Gynura bicolor DC.

Abstract: The compositions of the essential oils obtained from leaves and stems of Gynura bicolor DC. were analyzed by GC-MS. One hundred eight components of these oils were identified. (E)-β-caryophyllene (31.42 %), α-pinene (17.11 %), and bicyclogermacrene (8.09 %) were found to be the main components of the leaf oil, while α-pinene (61.42 %), β-pinene (14.39 %), and myrcene (5.10 %) were the major constituents of the stem oil. We found 73 previously unidentified components in these oils from G. bicolor. The oils were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…The leaf and stem oil inhibited AChE (53 %) at a concentration of 0.50 µg/mL with ID 50 values of 85 and 92 µg/mL, respectively. Both oils showed better results than pulegone [84]. EO obtained from fresh Chaerophyllum aromaticum L. root and aerial parts exhibited significant anticholinesterase and antioxidant activities [85].…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…The leaf and stem oil inhibited AChE (53 %) at a concentration of 0.50 µg/mL with ID 50 values of 85 and 92 µg/mL, respectively. Both oils showed better results than pulegone [84]. EO obtained from fresh Chaerophyllum aromaticum L. root and aerial parts exhibited significant anticholinesterase and antioxidant activities [85].…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Furthermore, we found that this aqueous extract at 2% and 4% displayed markedly antioxidative protection for human umbilical vein endothelial cells against high glucose induced damage. It is reported that the essential oil prepared from G. bicolor could inhibit acetylcholinesterase activity (Miyazawa and others ). The study of Teoh and others () revealed that chemical constituents of G. bicolor exhibited cytotoxic effects against colon carcinoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…Some monoterpenes, among them eugenol and menthol, inhibit the activity of acetylcholinesterase, which is the site of action of azamethiphos. But inhibition only occur when very high concentrations of the monoterpenes are applied; thus, it cannot be considered their primary site of action [33][34][35][36]. Nevertheless, an interaction involving this enzyme, which subsequently modifies its interaction with azamethiphos, cannot be overruled.…”
Section: Discussionmentioning
confidence: 99%